"Pleasing homogeneity," "Dull times," and "animated cocktails": New Zealand Architecture in the 1930s - McCarthy, Christine (Architectural History Aotearoa, 2006)
New Zealand in the 1930s began in mid-depression. Substantial rises in unemployment were recorded early in the decade, and an unemployment tax was introduced in 1930 to pay for unemployment relief. 1930 was also the same year that the beginnings of commerical aviation in New Zealand occurred. The first trans-Tasman airmail service dates from 1934, with TEAL (Tasman Empire Airways Ltd - now known as Air New Zealand) being established in 1939. This increasing significance of aviation in New Zealand during the decade was reflected in Hean's 1935 article "Airports" in the Journal of the New Zealand Institute of Architects. In 1931 relief camps were set up for the unemployed, and unemployed riots occurred in Auckland, Wellington and Dunedin. In June 1932 the NZIAJ noted that "[t]he almost complete cessation of building has had its inevitable result on employment of those connected with building - most of them are out of work, some are casually employed, and only a very few have any regular employment," while the following issue remarked that "[i]n the troublous times which have come upon us during the past fourteen years since the Armistice, not least among economic difficulties has been the high cost of building." This context lead to building subsidies and the Allied Building Industries Movement. By 1936 the normal working week was reduced from 44 hours to 40 hours.